POTENSI ALELOPAT DAUN PINUS (Pinus spp.) SEBAGAI BIOHERBISIDA PRA TUMBUH PADA GULMA KROKOT (Portulaca oleracea) - Lutfy Ditya Cahyanti; Titin Sumarni; Eko Widaryanto (Gontor AGROTECH Science Journal, 2015)
The aim of this experiment was to study the effectof pine leaf as allelophaty on purslane germination. Theexperiment were conducted at screen house Departmentof Biology, Faculty of Mathematics and Science, BrawijayaUniversity. The research is experimental design by nonfactorial Completely Randomized Blok Design, with threereplications, consisted of eleven levels. Purslane seeds sprout with control treatment, signifi cantly different from seedssprout ability in treatment solution leaves Pinus merkusii 2000ppm, and solution leaves of P. longaeva 2000 ppm. The resultshowed that 2000 ppm of P. merkusii extraction signifi cantlysuppressed 46% of purslane germination whereas 2000 ppmPinus longeava extraction signifi cantly suppressed of 41%campared to without any treatments (control).